Elusive Togetherness Church Groups Trying to Bridge America's Divisions. - Lichterman, Paul. (Princeton : Princeton University Press, 2011)
Many scholars and citizens alike have counted on civic groups to create broad ties that bind society. Some hope that faith-based civic groups will spread their reach as government retreats. Yet few studies ask how, if at all, civic groups reach out to their wider community. Can religious groups--long central in civic America--create broad, empowering social ties in an unequal, diverse society? Over three years, Paul Lichterman studied nine liberal and conservative Protestant-based volunteering and advocacy projects in a mid-sized American city. He listened as these groups tried to create bridg.
APPENDIX I: Theory and Evidence in a Study of Religious Community Service GroupsAPPENDIX II: Studying Customs; Notes; References; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; Y
Description based upon print version of record.
Keywords: Religion and social problems - United States; Social action - United States; Voluntarism - United States; Religion and social problems -- United States; Social action -- United States; Voluntarism -- United States; Associations, institutions, etc. -- United States; Small groups -- Religious aspects; SOCIAL SCIENCE / Sociology of Religion; Electronic books